A study of simulation and optimization of the production-reinjection scheme of a geothermal water system: A case study of the geothermal space heating demonstration area in northern Jiangsu countryside - Pengfei ZOU; Caihui WANG; Jianguo DU; Weiya GE; Zujiang LUO; Gang KONG; Yang QIU; Li LIU (Shuiwen dizhi gongcheng dizhi, 2023)
During the process of developing and utilizing geothermal resources, various challenges are encountered. One such challenge is the decrease in temperature and pressure of the geothermal reservoir as a result of the increasing geothermal exploitation and duration. In addition, the discharge of geothermal tail water poses a risk of thermal pollution, leading to environmental concerns. To address these issues effectively, reinjection of geothermal fluids into the reservoir can be implemented as a viable solution. Prior to initiating the geothermal development and utilization, it is crucial to conduct scientifical and rational planning of the layout of production and reinjection wells. This involves exploring optimal strategies for the production-reinjection scheme that prevents the premature thermal breakthrough and maximize the efficient utilization of geothermal resources, thereby extending the lifespan of the geothermal reservoir. The Fengpei Basin, a Cenozoic rift basin that developed since the Paleogene period, exhibits a widespread distribution of geothermal reservoirs, primarily composed of the Ordovician limestone with karst and fracture characteristics. Building upon the geothermal resource exploration results in the Anguo Town in Peixian County in Jiangsu Province, this study utilizes key parameters obtained from pumping tests and reinjection experiments, such as well spacing and the reinjection-to-production ratio. This paper establishes a 3D coupled numerical model of geothermal water seepage and heat transfer by using the Feflow6.2 software. The recoverable reserves of geothermal fluid within the geothermal reservoir are simulated and predictd, specifically the Ordovician limestone formation. Furthermore, a simulated optimization of the development and utilization scheme for the production-reinjection wells is conducted. The results reveal that an appropriate well spacing of 389 m between the producing well (RPX01) and the reinjection well (RPX02) is recommended. Moreover, the reinjection-to-production ratio, namely the ratio of average aquifer hydraulic conductivity, is determined to be 1.29, supporting a sustainable approach of one-for-one pumping and reinjection. With a stabilized drawdown of 50.61 m, the production well has a capacity to recover 1000 m3/d of geothermal resources. Under the conditions of a production rate and a reinjection rate of 1000 m3/d, as well as a reinjection temperature of 40 °C, the simulation predicts a decrease in groundwater level by 45.49 m and a temperature reduction of 1.44 °C after ten heating seasons. This represents the optimal cyclic development and utilization scheme among the simulated scenarios. The above results provide a scientific basis for decision-making in the construction of the clean energy heating demonstration area in rural northern Jiangsu. They contribute to the establishment of a scientifically sound and sustainable approach for utilizing geothermal resources, while considering the challenges associated with the thermal breakthrough and the environmental impact of geothermal tail water discharge.